Color transparency of Julian E. Davies and Bruce W. Holloway (1975)
Color transparency of Julian E. Davies (1932-) and Bruce W. Holloway (1928-) attending the 1975 Asilomar Conference. The Asilomar Conference on Recombinant DNA was an influential conference, organized by Paul Berg (1926-2023), that considered the potential biohazards of, and need to regulate, biotechnology. It was held in February 1975 at the Asilomar Conference Grounds in Pacific Grove, California. The conference was a milestone in the history of science, marking the beginning of attempts to study the social implications of scientific progress and to mitigate against negative social impact.
Keywords: Holloway, Bruce W., (Bruce William), 1928-; Davies, Julian E.; California--Pacific Grove--Asilomar Conference Grounds; Congresses and conventions; Biology--Congresses; Recombinant DNA--Congresses